O impacto do capital dos bancos na rentabilidade e risco no sistema financeiro brasileiro - Carbonari Filho, Antonio (2015)
Over the past few years, banks have always been present at the epicenter of the biggest financial crises. Adopting policies that reduce the occurrence of banking crises is important to ensure peace and security for its depositors and investors. Thus, policymakers adopted the capital as regulatory measure, which required banks greater control in relation to its risk assets. The capital also plays a fundamental role in the soundness and credibility of banks. Another important aspect of bank capital is its relationship with profitability and risk. With the capital increase, banks become less vulnerable to risk, ultimately reducing the occurrence of problems in a bank. Thus, the impact on profitability is positive in the profitability of banks, as it reduces their cost of funding and improve its perception in the market. Several studies relate capital to risk or profitability. The aim of this study, however, was to simultaneously analyze the impact of capital on profitability and risk in the Brazilian financial system. Four dependent variables of profitability and risk were used, and other explanatory variables such as those specific to banks, a measure of bank concentration and macroeconomic variables were also used. The study was conducted with the 50 largest banks considering the asset volume through a Generalized Method of Moments technique (GMM) between the period 2006-2014. The hypotheses relating the effect of capital on risk and profitability of banks showed positive results. Banks are benefited when they increase their capital with a positive impact on profitability variables. Furthermore, from the moment banks increase their risk, there is an adjustment in the level of capital upwards. Considering the importance of this sector for any economy, the study confirms the ability of Brazilian banks to prove themselves solid and profitable and at the same time taking the capital as an important factor of these achievements.